Factors Associated With Wandering Behaviors in Veterans With Mild Dementia: A Prospective Longitudinal Community-Based Study. Issue 2 (March 2018) - Barrett, Blake; Bulat, Tatjana; Schultz, Susan K.; Luther, Stephen L.
Objective: To investigate baseline factors associated with caregiver-reported wandering among community-dwelling veterans with mild dementia. Methods: Veterans with mild dementia (N = 143) and their caregivers participated in a 2-year prospective longitudinal study. Measures assessed wandering, daily function, behavior, cognition, and personality features. Wandering was dichotomized as present or absent across study periods, and associations with baseline characteristics were examined. Results: One-quarter of participants demonstrated caregiver-reported wandering at 1 or more study visits, with 14% to 15% wandering at any 1 visit. Wandering was associated with significantly lower baseline scores in performance of daily function, behavioral response to stress, gait, and balance, and conscientiousness. Conclusions: This novel study evaluated wandering in a community-dwelling sample of veterans with mild dementia. Wandering was associated with a specific personality trait, poorer behavioral response to stress as well as greater functional and gait/balance impairment. These findings may assist in developing community-based interventions for caregivers.